Evaluasi Sistem Informasi Akuntansi Penjualan Kredit: Studi Kasus MPM Motor Bondowoso - Muhammad Mufarrihul Fuad; Norita Citra Yuliarti; Rendy Mirwan Aspirandi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
At this time, information technology is increasingly experiencing developments that are in line with the development of human labor. Information technology has changed a lot in organizations and businesses. This study aims to find out and analyze whether the accounting information system on credit sales at PNM is adequate. The type of research used in this study is a qualitative approach. The object of this study is MPM Motor Bondowoso, a company engaged in the sale of motorcycles, spare parts and vehicle service. The results of this study show that the sales accounting information system at MPM Motor Bondowoso is categorized as quite good and adequate.